Water footprint assessment of water supply treatment process : a case study of Peramu water treatment plant - Sawiah, Nik Hassan (2016)
The instability changes of socio economic as well as monsoonal changes have long been tortured the water resource management system. Until to this date, water scarcity still being as the main issues globally. In Malaysia, several water shortages problems might be created from several factors. In this regard, the efficiency of our water supply system has raised the concern. Some studies have been made to assess the sustainability of our water supply such as by using Life Cycle Assessment (LCA). In this study, an attempt to use Water Footprint Assessment is carried out. This approach covers water utilization accounting during the treatment process. Therefore, the objectives of this study are to determine the water footprint for the in-line process of water supply treatment process and also how it is affected by the population, land use and monsoonal changes. The study area is at conventional water supply treatment process (WSTP) at Peramu, Pekan Pahang. The value of water footprint in each process of water supply treatment process is divide into WFblue, WFgreen and WFgrey. In addition to that, the effect of socio economic and monsoonal changes were also calculated and analyzed. From the results obtained, the monsoonal changes has affected the water footprint accounting. However, population and land use activities has the huge impact on water footprint accounting. So, the unregulated development whereby the water supply is from similar water intake would create water shortage.